The effects of national expenditure on economic growth in Netherlands / Nur Hidayah Abdullah - Abdullah, Nur Hidayah (2018)
National expenditure is a platform where a country should not feel like it is a burden because it can give good impact to the country if the government itself could handle it properly. Also, national expenditure could not be the causes of any bankruptcy. In fact, it is actually on of the reason a country could generate profit. This paper examines the effect of national expenditures on economic growth in Netherlands over the period from year 1987-2016. The dependent variable of this research is Gross Domestic Product (GDP) using four independent variable which are Military Expenditure (MIL), Gross Capital Formation (GCF), Import of Goods and Services (IMP), and Household and NPISHs Final Consumption (HOU). These independent variables are used to see whether there is significance or insignificance relationship with economic growth especially in household and NPISHs final consumption. The data is collected from World Development Indicators (WDI) with the data that had been used in this research is quantitative secondary data and the data structure is time series data. This paper used ordinary least squares (OLS) method which is a method to minimize an error. The findings indicate that the independent variable have positive relationship with GDP and HOU has the higher level impact in economic growth. The results of all the study suggest that greater national spending can provide better overall economic growth.